2020
DOI: 10.1111/cge.13719
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Wilson disease and Wilson‐like phenotype in a clinical series from eastern Spain

Abstract: Wilson's disease (WD) is an autosomal recessive disorder caused by ATP7B mutations. Subjects with only one mutation may show clinical signs and individuals with biallelic changes may remain asymptomatic. We aimed to achieve a conclusive genetic diagnosis for 34 patients clinically diagnosed of WD. Genetic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 10 publications
0
33
0
Order By: Relevance
“…Genetic analyses were performed using a customized panel with 498 genes involved in movement disorders (MovDisord-498) as previously described [47] and following filtering data criteria formerly reported in [48].…”
Section: Genetics and Bioinformaticsmentioning
confidence: 99%
“…Genetic analyses were performed using a customized panel with 498 genes involved in movement disorders (MovDisord-498) as previously described [47] and following filtering data criteria formerly reported in [48].…”
Section: Genetics and Bioinformaticsmentioning
confidence: 99%
“…Stratified genetic analysis is recommended in order to achieve a reasonable diagnostic success rate with the aim to cover the whole ATP7B sequence and the different possible mutation types [ 70 , 71 ]. First, it is advisable to perform the study of the 21 coding exons and flanking intron sequences, since they harbor the majority (~95%) of the clinical variants ( Table 2 ).…”
Section: A Mendelian Disease Caused By Mutations In Atp7bmentioning
confidence: 99%
“…Genetics analysis has the ability to provide early and accurate WD diagnosis. In a clinical series of WD in eastern Spain, Sánchez-Monteagudo et al identified biallelic ATP7B mutations in 30 patients, and in a case, a large deletion of exon 1 with MLPA (14). Our patient harbors a compound heterozygous mutation in the ATP7B gene.…”
Section: Discussionmentioning
confidence: 50%